PENGARUH KUALITAS PELAYANAN, KEPERCAYAAN DAN KEAMANAN TERHADAP LOYALITAS PEMBELI DI APLIKASI JD.ID PADA MASYARAKAT KOTA BATAM - Franky; Winda Evyanto (SCIENTIA JOURNAL, 2022)
Loyalty is the main key for buyers to continue to make a continuous purchase process for the company in the long term. Having a buyer means that a business managed by the company will run well. To achieve buyer loyalty, companies are encouraged to provide quality service and trust so that buyers feel satisfied. In addition, companies must also be able to improve security in order to avoid cyber crimes that will damage network systems and buyer data. This study aims to determine the effect of service quality, trust and security on buyer loyalty in the JD.ID application in the people of Batam City. This study uses a population and a sample of 200 buyers in the JD.ID application because the sampling technique uses a saturated sample technique. The data collection technique in this research is the distribution of questionnaires and this type of research uses quantitative methods. Respondents' answers in distributing questionnaires, the results of data processing were carried out through SPSS version 25 application software. The data analysis method used descriptive and inferential statistics. The results show that there is a significant and positive effect between service quality on buyer loyalty, there is a significant and positive influence between trust and buyer loyalty, there is a significant and positive effect between security and buyer loyalty, there is a significant and positive effect between service quality, trust and security. on buyer loyalty.